Detection of the Northeastern African Rift Valley Fever Virus Lineage During the 2015 Outbreak in Mauritania. (16th June 2017) - Bob, Ndeye Sakha; Bâ, Hampâté; Fall, Gamou; Ishagh, Elkhalil; Diallo, Mamadou Y.; Sow, Abdourahmane; Sembene, Pape Mbacké; Faye, Ousmane; El Kouri, Brahim; Sidi, Mohamed Lemine; Sall, Amadou Alpha
Abstract: Background: Rift Valley fever (RVF) is an acute viral anthropozoonosis that causes epizootics and epidemics among livestock population and humans. Multiple emergences and reemergences of the virus have occurred in Mauritania over the last decade. This article describes the outbreak that occurred in 2015 in Mauritania and reports the results of serological and molecular investigations of blood samples collected from suspected RVF patients. Methods: An RVF outbreak was reported from 14 September to 26 November 2015 in Mauritania. Overall, 184 suspected cases from different localities were identified by 26 health facilities. Blood samples were collected and tested by enzyme-linked immunosorbent assay (ELISA) and real-time reverse-transcription polymerase chain reaction (RT-PCR) at the Institut Pasteur de Dakar (IPD). Sequencing of partial genomes and phylogenetic analyses were performed on RT-PCR–positive samples. As part of routine surveillance at IPD, samples were also screened for dengue, yellow fever, West Nile, Crimean Congo hemorrhagic fever, Zika, and Chikungunya viruses by ELISA and RT-PCR. Results: Of the 184 suspected cases, there were 57 confirmed cases and 12 deaths. Phylogenetic analysis of the sequences indicated an emergence of a virus that originated from Northeastern Africa. Our results show co-circulation of other arboviruses in Mauritania—dengue, Crimean Congo hemorrhagic fever, and West Nile viruses. Conclusion: The Northeastern Africa lineage of RVF was responsible for the outbreak in Mauritania in 2015. Co-circulation of multiples arboviruses was detected. This calls for systematic differential diagnosis and highlights the need to strengthen arbovirus surveillance in Africa.